Enhancement of alkaline conductivity and chemical stability of quaternized poly(2, 6-dimethyl-1, 4-phenylene oxide) alkaline electrolyte membrane by mild temperature benzyl bromination. Issue 60 (6th October 2020) - Manohar, Murli; Kim, Dukjoon
Abstract : A series of quaternized polyphenylene oxide (QPPO) based alkaline electrolyte membranes with different degrees of quaternization were synthesized via a benzyl bromination method at mild temperature (75 °C). Abstract : A series of quaternized polyphenylene oxide (QPPO) based alkaline electrolyte membranes with different degrees of quaternization were synthesized via a benzyl bromination method at mild temperature (75 °C). Quite a high hydroxide conductivity under the reduced water uptake and swelling was exhibited by this method. When the degree of bromination measured from 1 H NMR analysis was 30%, the corresponding hydroxide ion conductivity was 0.021 S cm −1 . The chemical stability of the QPPO membranes was excellent, showing only 3% weight loss in 3 M NaOH solution during 1 month. The fuel cell performance test under H2 /O2 exhibited the power density of 77 mW cm −2 and the current density of 190 mA cm −2 at 70 °C. Such excellent properties of QPPO membranes resulted from the achievement of the quaternization at the benzyl position, specifically.